Investigation of the influence of workpiece-side parameters on the layer formation of zinc-coated boron-manganese steel - He, Franz; Merklein, Marion (Materials Research Proceedings, 2023)
The hot stamping process has been established as a technology for the production of ultrahigh-strength steel parts for safety-relevant components in lightweight construction for the automotive sector. Thanks to the reduced overall thickness combined with high tensile strength, it is possible to realize lightweight design concepts with improved crash behavior. Boron-manganese steels are usually used for this purpose. Due to initial process temperatures above 800 °C, hot stamping is considered a lubricant-free process. In addition to high friction and wear in the process, surface scaling and the need for tool repairs are the result. In light of these phenomena, hot stamping materials are coated to protect them from corrosion. Until now, aluminum-silicon-based coatings have been primarily used for the direct hot stamping route. While zinc-based coatings have so far mainly found usage in the indirect process route, they are now also become a valid alternative for the direct process route. In previous investigations, a significant influence of workpiece-side parameters on the formation of the coating during the austenitization process was found for aluminum-silicon (AlSi) coatings. In light of this, a similarly significant influence is suspected for zinc-based coatings. The parameters heating rate, furnace temperature and dwell time in the furnace and the effect on the coating formation of zinc-coated 20MnB8 during austenitization will be investigated. The resulting findings will form the basis for further experiments to investigate the influence of the parameters on friction and wear in the industry near strip drawing tests.
CRIS-Team Scopus Importer:2023-04-28
Keywords: 20MnB8; Coating; Hot Stamping